A non-collaborative approach for modeling ontologies for a generic IoT lab architecture. Issue 2 (17th February 2020) - Umaa Mageswari, S.; Mala, C.; Santhanavijayan, A.; Deepak, Gerard
Abstract: This paper describes the development of Domain Specific Ontologies for a Generic IoT Lab Architecture. A Non-Collaborative role-based ontology modeling paradigm along with ontology commitment evaluation has been proposed to increase the quality of IoT Ontologies. The proposed scheme follows a strategy of description based on the component level hierarchy. The paradigm incorporated follows the modeling of open-linked ontologies that represent fewer concepts and individuals to them allowing the semantic integration or alignment to each of these concepts.The proposed strategy axiomatizes using cardinality of instances and entities and their associations. An architectural perspective for Non-Collaborative Ontology Authoring for IoT Domain has been proposed. An average top-3 precision of 80% is achieved by the proposed ontology authoring mechanism.